IMPROVEMENT METHODICAL BASES COMPLEX ECONOMIC ANALYSIS OF THE BUILDING ENTERPRISE - R. T. Ismailov; N. F. Navruzbevova (Вестник Дагестанского государственного технического университета: Технические науки)
It is considered and elaborated contents and intercoupling main stage undertaking the complex economic analysis external and internal ambience of the building enterprise as the main means for reception lacking for decision making of information, all-round, packed and holistic reflecting condition and efficiency to economic activity of the building enterprise. They are offered principles to realization such main characteristic of the economic analysis as systematic, centrality of purpose, selectivity and validity got on his base of information.